Pastor Lukaš Dziekuć-Maliej and Great Evangelical Awakening in Belarus - Unučak, Andrėj Uladzimiravič 1978- (2025)
This article is devoted to the Belarusian Baptist pastor Lukaš Dziekuć-Maliej (1888-1955) and his work in the context of the Great Evangelical Awakening in Belarus. The first part of the article describes his origins, his conversion and the beginning of his ministry. The second part is devoted to Maliej’s life and work in Hrodna (1915/1916-1921), during which he was actively involved in the Belarusian national revival, the restoration of Belarusian statehood and the founding of Belarusian schools. Maliej’s enforced but very blessed period as a minister in Brest (1921-1939) is the subject of the third part of the article. This time in Belarusian history is called the era of the Great Evangelical Awakening and the Baptist Church in Brest, whose pastor Maliej was, became one of the largest in Eastern Europe. Maliej translated the New Testament and the Psalms and thanks to his efforts, the evangelical faith became part of the Belarusian identity.
Keywords: Belarus; Belarusian translation of the Bible; Brest; Brest Baptist Church; Great Evangelical Awakening in Belarus; Hrodna; Lukaš Dziekuć-Maliej